Analyzing the Impact of Financial Liberalisation on Malaysian Bank's Performance: Quantile Regression Analysis - Nur Afizah Muhamad Arifin; Ismah Osman; Norhasimah Shaharuddin; Fauzias Mat Nor (Information Management and Business Review, 2024)
This study employs quantile regression analysis to examine the impact of financial liberalization on the performance of Malaysian banks, focusing on how these effects vary across different performance levels. A liberalized banking sector prompted commercial banks to intensify risk-taking activities, which ultimately could affect the bank’s performance. Using quantile regression analysis, it shows that only the middle quantile indicates all the significant variables for both OLS and quantile analysis. This study found that lower-performing banks may face adverse effects, including increased risk and deteriorating performance, due to heightened financial liberalization. The findings highlight the differential impact of financial liberalization across the performance spectrum and suggest that while liberalization can drive economic growth targeted regulatory measures are necessary to support less and mitigate potential risks to overall financial stability in Malaysia.